RETIME software for real time data acquisition using LEICA TCA series - Abbas, Mohd. Azwan (2006)
Industrial survey is a discipline of engineering surveys that requires the utmost in achievable accuracies and real time data processing. The instrumentation used in conventional industrial survey requires long painstaking procedures with very skilled craftsmen to obtain the required results. Revolution of technology with the introduction of new instruments (such as total station, computer and software) has revolutionized industrial survey. The development of three dimensional (3D) coordinating system and total station interfaced to a microcomputer provides the capabilities for on line data gathering with simultaneous processing in 3D. This research concentrates on the development of software to acquire data from robotic total station (RTS) TCA2003 in real time. This software called RETIME is a short form of REal TIME. RETIME software consisted of the three core module i.e. (i) Data communication with RTS TCA2003, (ii) Calculate the raw data to produce 3D coordinates, and (iii) Convert the data from RETIME format into STAR*NET format. STAR*NET software (third party software) has been used in this research to provide an adjusted data. For verification purpose, RETIME software has been evaluated and the resulted are acceptable for industrial survey environment.